Effect of feedstock particle size distribution and feedstock moisture content on pellet production efficiency, pellet quality, transport and combustion emissions. (1st March 2020) - Labbé, Rodrigo; Paczkowski, Sebastian; Knappe, Victoria; Russ, Michael; Wöhler, Marius; Pelz, Stefan
Highlights: Sawdust with different particle size distribution and water contents was produced and pelletized. The pellet properties showed differences according to the feedstock particle size distribution and water content. The pellet combustion profile in a pellet stove correlated to the feedstock particle size distribution. The presence of long fibers in the feedstock improve both pellet quality and combustion behavior. Abstract: This study evaluates the possibility of reducing drying costs by screening large particles prior to drying and pelletizing them with the dried medium size and fine particles. Four feedstocks with different shares of fibers (>3.15 mm) and fines (<1 mm) were conditioned at 12 and 24% water content (wc). Bulk density, durability, length and water sorption behavior of the pellets were evaluated. Transport costs, energy consumption and greenhouse gas emission equivalents were calculated. The combustion behavior was correlated to the particle size distribution of the feedstock. The 24%wc feedstock pellets (P24 ) showed a low durability ( x ¯ = 79%). The P24 with the highest share of large particles showed the highest durability ( x ¯ = 89%). Large particles caused pellets with high durability and fines caused pellets with low durability. All P12 had lower transport costs, lower energy consumption and lower greenhouse gas emissions in comparison to the P24, because their bulk density was higher (619 kg × m −3 and 362 kg × m −3, respectively). The combustion parameters of the P12 were affected by the feedstock particle size distribution. The Fpsd with the highest share of particles in the range of 3.15–6.30 mm showed the highest durability ( x ¯ = 98.5%) and the lowest CO emissions ( x ¯ = 280 mg/m 3 ). The calculated costs for a combined screening/drying process were lower than the costs for conventional drying. A new production concept is proposed: Large particles can be screened before drying and can be mixed with the dried medium/small size particles for pelletization.